(C4H12N2)[CoCl4]: tetrahedrally coordinated Co2+ without the orbital degeneracy. Issue 1 (1st February 2015) - Decaroli, C.; Arevalo‐Lopez, A. M.; Woodall, C. H.; Rodriguez, E. E.; Attfield, J. P.; Parker, S. F.; Stock, C.
<x xml:space="preserve">Abstract</x> We report on the synthesis, crystal structure and magnetic properties of a previously unreported Co2+<inline-graphic xlink:href="ark:/27927/pgh3r5gww90" mimetype="image" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /> compound, (C4H12N2)[CoCl4], based upon a tetrahedral crystalline environment. The <inline-graphic xlink:href="ark:/27927/pgh3r5gww90" mimetype="image" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /> magnetic ground state of Co2+, measured with magnetization, implies an absence of spin‐orbit coupling and orbital degeneracy. This contrasts with compounds based upon an octahedral and even known tetrahedral Co2+ [Cotton et al. (1961). J. Am. Chem. Soc.83, 4690] systems where a sizable spin‐orbit coupling is measured. The compound is characterized with single‐crystal X‐ray diffraction, magnetic susceptibility, IR and UV–vis spectroscopy. Magnetic susceptibility measurements find no magnetic ordering above 2 K. The results are also compared with the previously known monoclinic hydrated analogue.